2022
DOI: 10.1021/acsptsci.1c00257
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Targeting of Cancer Stem Cells Prevents Resistance of Colorectal Cancer Cells to MEK Inhibition

Abstract: Drug resistance is a leading cause for the failure of cancer treatments. Plasticity of cancer cells to acquire stem cell-like properties enables them to escape drug toxicity through different adaptive mechanisms. Eliminating cancer stem cells (CSCs) can potentially improve treatment outcomes for patients. To determine the role of CSCs in resistance of colorectal cancer cells to targeted therapies and identify treatment strategies, we treated spheroids of BRAFmut and KRASmut colorectal cancer cells with inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 67 publications
4
7
0
Order By: Relevance
“…Organoids cultured from Apc Min/+ mice had increased expression of Ctnnb1 , Axin2 , and Lgr5 following treatment with the MEK inhibitor U0126 as compared to the vehicle control (fig. S20H), consistent with previous studies ( 51 , 52 ).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Organoids cultured from Apc Min/+ mice had increased expression of Ctnnb1 , Axin2 , and Lgr5 following treatment with the MEK inhibitor U0126 as compared to the vehicle control (fig. S20H), consistent with previous studies ( 51 , 52 ).…”
Section: Resultssupporting
confidence: 92%
“…Organoids cultured from Apc Min/+ mice had increased expression of Ctnnb1, Axin2, and Lgr5 following treatment with the MEK inhibitor U0126 as compared to the vehicle control (fig. S20H), consistent with previous studies (51,52). Ku70 senses cytosolic DNA and forms a signalosome at the endosome Previous studies have shown that patients with ulcerative colitis have more nuclear-and mitochondria-free (cell-free) DNA in the plasma than healthy controls (53,54).…”
Section: Ku70 Translocates To the Cytoplasm And Interacts With Ras An...supporting
confidence: 89%
See 2 more Smart Citations
“…Mithramycin (Mit-A), an antineoplastic antibiotic known to inhibit RNA synthesis and produced by Streptomyces plicatus, is one such promising compound . Mit-A has been shown to have antitumor effects by targeting cancer stem cells in various cancers. Mit-A has demonstrated significant inhibition of GBM invasiveness by targeting the GSC transcription factors SOX2, OLIG2, and ZEB1 in glioma . Additionally, Mit-A treatment reduced cell migration in gliomas by altering MMP-2 and 9, VEGF, and RON kinase .…”
mentioning
confidence: 99%